Effects of Normal Reference Range of Phosphorus and Corresponding PTH on Endothelial Function in CKD Patients - Lee, Shina; Kim, Seung-Jung (Frontiers in Medicine, 2022)
Introduction: Endothelial dysfunction commonly occurs in chronic kidney disease (CKD) patients and increases the risk for cardiovascular disease. Among CKD patients, biomarkers involved in the pathogenesis of CKD-mineral bone disorder (CKD-MBD), such as phosphorus, parathyroid hormone, and fibroblast growth factor 23, are associated with endothelial dysfunction. We investigated whether these biomarkers induce endothelial dysfunction in CKD patients with normal phosphorus levels. Methods: This cross-sectional study examined CKD patients with normal phosphorus levels; patients with an estimated glomerular filtration rate (eGFR) < 15 or who were under dialysis were excluded. Iontophoresis with laser doppler flowmetry (ILDF) and peripheral arterial tonometry were performed to assess endothelial function in 85 patients. Pearson’s correlation coefficient, multiple regression, and mediation analyses were performed to examine the association between CKD-MBD biomarkers and endothelial dysfunction. Results: Endothelial dysfunction was observed in all subjects with a low response to ILDF and 27% of subjects according to peripheral arterial tonometry. Acetylcholine (Ach)-induced ILDF was significantly associated with eGFR (r = 0.22, P = 0.04), intact parathyroid hormone (iPTH; r = –0.46, P < 0.01), and VCAM-1 (r = –0.36, P < 0.01). The reactive hyperemia index (RHI) was significantly related to phosphorus levels (r = 0.32, P < 0.01) and iPTH (r = –0.39, P = 0.02). After adjusting for eGFR, iPTH and VCAM-1 remained independent factors for predicting endothelial dysfunction measured using Ach-induced ILDF. In addition, iPTH and phosphorus levels were independent predictors for endothelial dysfunction measured using RHI in the eGFR-adjusted model. Mediation analyses showed that the individual indirect effects of iPTH were significantly affected ILDF and RHI. Conclusion: Serum levels of phosphorus and iPTH are associated with endothelial dysfunction, even in CKD patients with normal phosphorus levels.